Polinización en Bactris gasipaes H.B.K. (Palmae) - Mora Urpí, Jorge; Solís, Emilia María (Revista de Biología Tropical, 1980)
A study on pollination of the pejibaye palm (Bactris gasipaes H.B .K.) was carried out in Costa Rica at two localities with different·ecological conditions (San Isidro de El General and Guápiles) during two flowering seasons (1976-1977 and 1977-1978). In San Isidro de El General the flowering peak comes in February during the dry season and in Guápiles it takes; place in July under steady rains. These climatic differences alter to a certain degree the importance of insect and wind pollination as described below. This monoecius palm bears both pistilate and staminate flowers; in the same inflorescence. It has a pollination cycle of three days. Female anthesis coincides with the opening of the bract at approximately 5:30 p.m. on the first day of the cycle. These pistilate flowers retain some degree of fertility up to when male anthesis occurs 24 hours later. This completes the second day of the cycle. Some of the pollen released at the time of male anthesis remains on the rachillae of the inflorescence until the following morning, i.e., the third day of the cycle, when it is sufficiently dried to be carried away by the wind. There are three agents responsible for pollination in pejibaye: insects, wind and gravity. Pollination by the curculionid Derelomus palmarum Champ. is the most important. These insects arrive at a freshly opened inflorescence carrying pollen from one more mature that is undergoing male anthesis. Several aspects of insect pollination indicate a certain degree of specialized coevolution between Derelomus and Bactris. Wind as a pollination agent is less effective, however, because of the random distribution of the pollen and its rapidly diminishing concentration within a short distance. Wind is essentially the only agent which transmits the pollen present on the rachillae on the morning of the third day of the cycle. Both of these types of pollination favor exogamy, but some geitonogamy will also occur. Pollination by gravity takes place during male anthesis on the second day, favoring endogamy. Its effectiveness however, is greatly reduced by two factors: one, the prior exposure of the female flowers to pollen from insects and wind and, second, to the presence of a genetic self incompatibility system. The cromosome number (2n=28) and the germination of pollen on a 5% glucose solution are reported.